Klebsiella pneumoniae-Isolation, Identification and Characterization from Naturally Infected Farmed Raised Nile Tilapia Oreochromis niloticus (Linnaeus, 1758) in West Bengal, India - Meshram, Supradhnya Namdeo; Abraham, T. Jawahar (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted in 2015 (March–May, 2015) at aquatic animal health laboratory, Faculty of Fishery Sciences, Kolkata, West Bengal, India. Klebsiella pneumonia was a rod-shaped, Gram-negative, and facultative anaerobic bacterium. It was widespread in nature and found in many environments such as soil, plants, industrial effluent, sewage, surface water and drinking water. It was one of the important human pathogens, causing most commonly pneumonia, typically bronchopneumonia and bronchitis. However, there were few reports suggesting its potential role as an aquatic pathogen. It was an opportunistic pathogen and was usually present in the normal microbiota of fish but causes diseases in favourable conditions such as low water quality. The present study reported the occurrence of disease in Oreochromis niloticus caused by K. pneumoniae. The infected fish showed clinical signs such as lethargy, anorexia, gill discoloration, fin/tail rot, subcutaneous haemorrhages and ascites. Bacteria were isolated from the kidney and confirmed as K. pneumoniae (Accession no. OQ789963) by morphological evaluation, biochemical tests and nucleotide sequence of 16S rDNA. To observe pathological changes in tissue level, the kidney, brain, liver and spleen were selected for histopathology. The vital organ and kidney sections showed melano-macrophage aggregate, glomerulopathy, inflamed nephritic tubules, degeneration of nephritic tubules, and cellular hypertrophy. The brain exhibits inflamed neurons, haemorrhage, granuloma-like structure and cerebellum with sponge-like appearance. With the findings of this study, the systemic pathogenesis both on the external body parts as well as in internal organs of O. niloticus by K. pneumoniae infection was elucidated.